Role of Babesia microti Surface Antigen 1 and its Interaction with Erythrocytes in Babesiosis - Hegde, Shreeya. (2018)
Abstract: Human babesiosis is a malaria-like disease highly prevalent in North East America that can be fatal to the elderly and immune-compromised subjects. However, relatively little is known about the molecular mechanisms of the disease. Babesia microti Surface Antigen 1 (BmSA1) is a membrane/secreted protein that has been previously identified and characterized, but its functional role in parasite invasion and growth as well as its potential as a vaccine candidate remains to be determined. To test the role of BmSA1 in parasite invasion, we re-evaluated published methods of in vitro invasion assays to find optimal conditions for the quantification of parasitemia. Surprisingly, despite multiple attempts and shared reagents, we could not reproduce published in vitro invasion assays. Alternatively, we established an in vitro growth assay to quantify intraerythrocytic development of Babesia microti, the most common causative agent of human babesiosis in North America. Using the in vitro growth assay, we tested the effects of recombinant BmSA1 protein, Signal Peptide Peptidase (SPP) inhibitor, Z-LL2 ketone, and HIV protease inhibitors, Atazanavir and Lopinavir on parasite development in erythrocytes. Both single and combination protocols were used to test the efficacy of potential inhibitors. Remarkably, the Z-LL2 ketone potently inhibited B. microti growth in human erythrocytes, and other test molecules also showed significant inhibitory effects under these conditions. Furthermore, to identify the host erythrocyte receptor for BmSA1, I performed multiple phage display screens using the human reticulocyte cDNA library and far western blotting of RBC membrane proteins. Our screens suggest that BmSA1 can recognize two potential receptors in human erythrocyte membranes of molecular mass ranging within 200-245 kDa and 48-50 kDa. Together, these studies set the stage for molecular identification of host receptor for BmSA1 as well as development of potential therapeutics for human babesiosis.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Athar Chishti.; Keyword: Pharmacology.